BUSINESS MODEL CANVAS UNTUK MENGEMBANGKAN STRATEGI BISNIS KERIPIK PISANG (STUDI KASUS UKM SELERAKU DI KABUPATEN BANJARNEGARA) - Sarno Sarno; Eko Apriliyanto (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2021)
One of the business models used to develop a banana chips business strategy is the canvas business model. The purpose of this research is to find out how to apply the business model canvas and the customer emphaty map and the design of its transformation to develop the banana chips business strategy of Seleraku Banjarnegara UKM. The research method used is participatory action research and descriptive analysis. Data analysis used analysis of the business model canvas and the customer emphaty map. The research results are as follows; (1) business model canvas to develop a banana chip business strategy at Seleraku Banjarnegara SMEs, customer segments include children to the elderly, healthy snack/snack consumers, and resellers with value propositions covering the quality of raw materials, healthy snacks/snacks, and products easy to find. The company uses direct sales channels and reseller and customer relationships in the form of excellent and professional service for customers. Key activities include production and marketing activities by utilizing key resources which include human, physical and intellectual resources. The key partnership consists of banana farmers and resellers. The company generates revenue streams from the sale of banana chips as the main product with cost structures consisting of fixed costs and variable costs, (2) the design of business model transformation as a company development strategy needs to be done while maintaining the current channels and key resources. Additions were made to value propositions in the form of delivery order services. The use of social media in customer relationships, generates revenue streams from the sale of banana peel chips, adds social activities to key activites, adds partners consisting of distributors, event organizers and delivery services for key partnerships, and increases costs for social activities on cost structures.